2000
DOI: 10.1093/jjco/hyd077
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Response Patterns of Alveolar Macrophages from Patients with Lung Cancer by Stimulation with Interferon-gamma

Abstract: The AM have anti-tumor cytotoxicity in lung cancer although the cytolytic potential is heterogeneous and that the tumor lysis by AM is mediated by both TNF-alpha and NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Others have shown AM from patients with primary lung cancer suppressed chemotaxis and this intrinsic functional defect is more pronounced on AM from the local tumour site compared to the opposite side of the lung [3]. Eifuku et al [11] reported heterogeneous cytotoxic function of BAL AM in patients with lung cancer and suggested that the heterogeneity of response likely reflected variations in activation state of AM. Heterogeneity in cytotoxicity against the squamous cell lung cancer cell line QG56 was also noted in response to IFN‐γ stimulation in this study, where AM cytotoxic potential paralleled AM IL‐1 secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown AM from patients with primary lung cancer suppressed chemotaxis and this intrinsic functional defect is more pronounced on AM from the local tumour site compared to the opposite side of the lung [3]. Eifuku et al [11] reported heterogeneous cytotoxic function of BAL AM in patients with lung cancer and suggested that the heterogeneity of response likely reflected variations in activation state of AM. Heterogeneity in cytotoxicity against the squamous cell lung cancer cell line QG56 was also noted in response to IFN‐γ stimulation in this study, where AM cytotoxic potential paralleled AM IL‐1 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in up‐regulation of costimulatory molecules CD80 and CD86 have been observed in AM from patients with allergies [35] however, this has not been assessed in primary lung cancer patients. Phenotypic analysis suggests that there is no difference between CD68 and HLA‐DR expression in AM from lung cancer patients compared to controls however, a significant increase in CD11c, CD11b and CD11a was observed [11]. The ability of AM to stimulate T cells will include the phenotype of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased TNF- α and IL-1 secretion from AMs of patients with lung cancer after stimulation with IFN- γ and granulocyte-macrophage colony-stimulating factor (GM-CSF) has been demonstrated in comparison with patients with nonmalignant disorders [ 7 ]. IL-1 mediates cytotoxicity and suppression of tumour growth [ 31 , 32 ] and TNF- α inhibits angiogenesis to prevent tumour growth. TNF- α can therefore act as an antitumour monokine and be responsible for spontaneous (without external activation) cytotoxic effects of AMs [ 33 ].…”
Section: Potential Role Of Alveolar Macrophages In Tumour Regressimentioning
confidence: 99%
“…Numerous studies have isolated AMs from bronchoalveolar lavage (BAL) for assessment of their function in the presence of known macrophage-activating agents such as IFN- γ and GM-CSF [ 8 , 13 , 15 , 31 , 34 ]. IFN- γ stimulates IFN- γ inducible protein (IP-10), an antitumour molecule that impairs tumour angiogenesis, whereas GM-CSF promotes proliferation of haematopoietic progenitor cells and influences the antitumour function of AMs [ 34 ].…”
Section: Potential Role Of Alveolar Macrophages In Tumour Regressimentioning
confidence: 99%
“…23). In vitro attempts to stimulate production of NO⅐ by human monocytes have failed, and the study of NO⅐ production by human AMs has been confined to systems in which these cells are already stimulated, such as idiopathic pulmonary fibrosis (36) and cancer (12).…”
Section: Killing Of Pathogens By Human and Murine Alveolar Macrophagementioning
confidence: 99%